Porcine Brachial Artery Tortuosity for In Vivo Evaluation of Neuroendovascular Devices - Carniato, S.; Mehra, M.; King, R.M.; Wakhloo, A.K.; Gounis, M.J. (American Journal of Neuroradiology, 2013)
SUMMARY: We report a novel model of arterial tortuosity in the porcine brachial artery for testing of endovascular devices in the flexed forelimb position. This provides an ideal vascular territory for an in vivo assessment of guidewires, microcatheters, and endovascular implants because it closely mimics the challenging curvature at the carotid siphon. ACaverage curvature3DRA3D rotational angiographyCCAcommon carotid artery